Upgrading Traditional Techniques of Food Fermentation: Kabuto-Making - Susilowati, Prima Endang; ., Sanatang; Safitri, Meilani; Raharjo, Sapto (International Journal of Science, Engineering, and Sustainable Technology (IJSESTech), 2014)
The capacity to preserve food is directly related to the level of technological development. The slow progress in upgrading traditional food processing and preservation techniques in Sulawesi Tenggara contributes to food and nutrition insecurity in the sub-region. Simple, low-cost, traditional food processing techniques are the bedrock of small-scale food processing enterprises that are crucial to rural development in Sulawesi Tenggara. While a lot still needs to be done, some successes have been achieved in upgrading traditional sulawesi Tenggara food processing technologies including the mechanization of kabuto (fermented cassava meal) processing.